2022
DOI: 10.1073/pnas.2118931119
|View full text |Cite
|
Sign up to set email alerts
|

Persistent soil carbon enhanced in Mollisols by well-managed grasslands but not annual grain or dairy forage cropping systems

Abstract: Intensive crop production on grassland-derived Mollisols has liberated massive amounts of carbon (C) to the atmosphere. Whether minimizing soil disturbance, diversifying crop rotations, or re-establishing perennial grasslands and integrating livestock can slow or reverse this trend remains highly uncertain. We investigated how these management practices affected soil organic carbon (SOC) accrual and distribution between particulate (POM) and mineral-associated (MAOM) organic matter in a 29-y-old field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 64 publications
(84 reference statements)
0
43
0
Order By: Relevance
“…Thus, the increased SOC stock under the pasture and the associated contribution from MAOM-C in Rui et al. ( 1 ) could be detected only for the topsoil, where plant C inputs are the highest. Moreover, SOC stock is positively correlated with the content of amino sugars solely in the topsoil, but it is negatively correlated with N -acetyl-β- d -glucosaminidase and polyphenol oxidase activities in the subsoil ( Fig.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, the increased SOC stock under the pasture and the associated contribution from MAOM-C in Rui et al. ( 1 ) could be detected only for the topsoil, where plant C inputs are the highest. Moreover, SOC stock is positively correlated with the content of amino sugars solely in the topsoil, but it is negatively correlated with N -acetyl-β- d -glucosaminidase and polyphenol oxidase activities in the subsoil ( Fig.…”
mentioning
confidence: 78%
“…Rui et al. ( 1 ) reported that perennial pasture with rotational grazing significantly increased soil organic carbon (SOC) stock at 0 to 30 cm by 15 to 28% compared to conventional continuous annual cropping systems in a 29-y field experiment in the north-central United States. We applaud their efforts in managing such a valuable long-term experiment as well as revealing the intriguing potentials to enhance SOC stock by promoting land conversion from annuals to perennials with optimized management.…”
mentioning
confidence: 99%
“…( 1 ) argue that “SOC stock is positively correlated with the content of amino sugars solely in the topsoil, but it is negatively correlated with N -acetyl-β- d -glucosaminidase and polyphenol oxidase activities in the subsoil.” Table S5 of ref. 2 showed the correlations between MAOM-C concentrations, not SOC stock, with soil microbial attributes. We believe using SOC or MAOM-C stock can help with soil C accounting purposes, but to unravel mechanistic relationships with soil microbial attributes it would be better to use SOC or MAOM-C concentrations.…”
mentioning
confidence: 97%
“…Chen et al. ( 1 ) provide valuable feedback on our paper ( 2 ), suggesting that our work overestimated soil organic carbon (SOC) benefits of certain systems because we lacked data below 30-cm soil depth. In our paper, we acknowledged the uncertainties associated with deep soil C stocks, making no claim that our observations applied to deeper soils.…”
mentioning
confidence: 99%
See 1 more Smart Citation